Psychological Capital and Well-Being beyond the Workplace: A Conceptual Review - Fayaz Ahmad Paul; Indrajeet Banerjee; Arif Ali (Indian Journal of Psychiatric Nursing)
Psychological capital (PsyCap) is an individual's psychological capacity that can be measured, improved, and managed for performance improvement. Hope, self-efficacy, optimism, and resilience are among the psychological resources that make up the higher-order construct. It has been connected to a variety of positive work attitudes, behaviors, and other outcomes. The concept of well-being is intricately joined with that of living life to the fullest potential. The decades of extensive research on mental illness and dysfunctional behavior in psychology and other behavioral science have generally failed to contribute to a better understanding of the role that human qualities, flourishing, and optimal performance. Similarly, the study of work stress, conflict, dysfunctional attitudes, and other negative constructs that have preoccupied organizational behavior and human resource management scholars and practitioners has also not necessarily shed more light on the traits of outstanding workers or the dynamic mechanisms that support greatness in the workplace. This realization motivated positive psychologists and positive organizational behavior scholars to launch new and exciting streams of research that focus on positivity in its own right, rather than simply extrapolating existing mainstream research. It is expected that the positive influences of PsyCap will reduce costs and mitigate negative influences in an organization or workplace. The concept of well-being is a complex thought on optimal performance in one's life. It is having two visual aspects, the hedonic approach and the eudaimonic approach. The present conceptual review paper has been drafted to have an understanding of positivity, particularly PsyCap which can promote well-being, both at and beyond the workplace.